A preliminary report on two floral variants in the 1981 wild Hevea germplasm collection - Madhavan J; Abraham S T; George P J; Reghu C P (Indian Journal of Natural Rubber Research, 1997)
Floral morphological studies on the 1981 IRRDB wild Hevea germplasm collection maintained at the Rubber Research Institute of India have revealed two genotypes which are different from the rest. These variants differ in the pattern of growth, colour of the flower, presence of a disk at the base of the staminal column in the male flower and morphology of the fruit. The possibility of these being infraspecific variants or interspecific hybrids is discussed.
Keywords: Floral mmorphology; Floral mmorphology; Fruit morphology; Fruit morphology; Hevea species; Hevea species; Taxonomy; Taxonomy; Wild germplasm; Wild germplasm